Association Between Penile Dynamic Contrast‐Enhanced MRI‐Derived Quantitative Parameters and Self‐Reported Sexual Function in Patients with Newly Diagnosed Prostate Cancer. (1st October 2014) - Vargas, Hebert Alberto; Donati, Olivio F.; Wibmer, Andreas; Goldman, Debra A.; Mulhall, John P.; Sala, Evis; Hricak, Hedvig
Abstract: Introduction: The high incidence of prostate cancer, coupled with excellent prostate cancer control rates, has resulted in growing interest in nononcological survivorship issues such as sexual function. Multiparametric magnetic resonance imaging (MRI) is increasingly being performed for local staging of prostate cancer, and due to the close anatomical relationship to the prostate, penile enhancement is often depicted in prostate MRI. Aim: To evaluate the associations between quantitative perfusion‐related parameters derived from dynamic contrast‐enhanced (DCE)‐MRI of the penis and self‐reported sexual function in patients with newly diagnosed prostate cancer. Methods: This retrospective study included 50 patients who underwent DCE‐MRI for prostate cancer staging before prostatectomy. The following perfusion‐related parameters were calculated: volume transfer constant (K trans ), rate constant (kep ), extracellular‐extravascular volume fraction (ve ), contrast enhancement ratio (CER), area under the gadolinium curve after 180 seconds (AUC180), and slope of the time/signal intensity curve of the corpora cavernosa. Associations between perfusion‐related parameters and self‐reported sexual function were evaluated using the Wilcoxon Rank‐Sum test. Main Outcome Measures: Patient responses to the sexual function domain of the Prostate Quality of Life survey. Results: Five of the six DCE‐MRI parameters (K trans, ve, CER, AUC180, and slope) were significantly associated with the overall score from the sexual domain of the survey ( P = 0.0020–0.0252). CER, AUC180, and slope were significantly associated with the answers to all six questions ( P = 0.0020–0.0483), ve was significantly associated with the answers to five of six questions ( P = 0.0036–0.1029), and K trans was significantly associated with the answers to three of six questions ( P = 0.0252–0.1023). kep was not significantly associated with the overall survey score ( P = 0.7665) or the answers to any individual questions ( P = 0.4885–0.8073). Conclusion: Penile DCE‐MRI parameters were significantly associated with self‐reported sexual function in patients with prostate cancer. These parameters are readily available when performing prostate MRI for staging and may be relevant to the management of patients considering prostate cancer therapies.